Impact of adherence to GOLD guidelines on symptom prevalence, lung function decline and exacerbation rate in a Swiss COPD cohort (Swiss Medical Weekly, 2012)
PRINCIPLES: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines aim to optimise chronic obstructive pulmonary disease (COPD) diagnosis and treatment. However, little is known about the extent to which general practitioners’ (GP) adherence to GOLD guidelines improves patient outcomes. METHODS: In this questionnaire-based study, COPD patients were screened and enrolled; exacerbation history was recorded, and demographic, spirometric and management data were collected for 12 months. Spirometry was performed at least every 6 months according to American Thoracic Society guidelines. Based on these data, patients were grouped into GOLD COPD severity classifications. Data were expressed as the difference between baseline and month 12. RESULTS: Among 139 GPs, 454 patients were analysed regarding baseline and 12 month data. There was no significant change in distribution of GOLD COPD severity grades, lung function or guideline adherence. Chronic cough and sputum production were significantly reduced (p